High-Dimensional Sparse Structured Input-Output Models, with Applications to GWAS (Practical Applications of Sparse Modeling, 2014)
This chapter contains sections titled: 1 Problem Setup and Notations, 2 Structured Penalty on the Inputs, 3 Optimization Algorithms, 4 Comparison of Optimization Procedures, 5 Structured Output Regression for Correlated Phenome Association, 6 Structured Input Regression for Correlated Genome Association, 7 Structured Input-Output Regression for Genome-Phenome Association, 8 Summary, Note, References